AN ASSESSMENT OF THE UPTAKE OF LEAD ACETATE ON Oreochromis niloticus (AFRICAN TILAPIA - Nwakanma, C.; Esinwoke, P. C.; Vincent-Akpu, I. F.; Daniel-Igwe, G. (Nigerian Journal of Fisheries, 2018)
An assessment of the concentrations of lead acetate in the gills of Tilapia (Oreochromis niloticus) samples collected from a fishpond in Michael Okpara University of Agriculture, Umudike, Abia State was carried out in this study. The levels of heavy metal concentration on the gills were relatively higher compared to other body parts which may be attributed to the fact that the gills are the route of uptake of water (which invariably serves as the medium of entry). Photomicrography from gills of Oreochromis niloticus exposed to lead acetate showed prominent secondary lamella with moderate epithelial necrosis and marked congestion of venous sinuses, scant pillar cells, and mucous cells. Correlations between metal concentrations and fish size were not significant (P<0.05). Although, the level of bioaccumulation of Lead (Pb) generally did not exceed the safe level for human consumption. However, the constant presence of heavy metal in concentrations closer to limits (0.2 mg/kg of fresh weight) should be a reason for concern. The study further advised the populace who constantly consume fish from polluted rivers to avoid eaten the gills and reduce consumption.